An unusual thrombolytic therapy decision in prosthetic valve thrombosis during early pregnancy - Erkan Köklü; İsa Öner Yüksel; Zehra Erkal; Selçuk Küçükseymen; Şakir Arslan (KARE Publishing, 2015)
Pregnancy is among the risk factors for mechanical valve thrombosis, and even though thrombolytic therapy is contraindicated during pregnancy, it may be used in the treatment of this life-threatening complication. This case report describes a pregnant patient, whose echocardiogram showed evident gradient increase on her mechanical prosthetic mitral valve, and who was treated successfully with tissue plasminogen activator for mechanical valve thrombosis.